(untitled) (International Journal of Food and Nutritional Sciences, 2022)
There has been an increased interest in the use of information technology for health and health care delivery. This systematic review examines patterns and trends of research pertaining to the intersection between technology and health communication, determines where gaps exist within the current body of literature, and provides future directions for researchers and practitioners.